A constitutive model for a novel modular all-steel buckling restrained brace. (1st October 2015) - Piedrafita, D.; Maimí, P.; Cahis, X.
Highlights: We propose a material model for predicting the behaviour of elastoplastic dissipators. A variable controls the ratio between the isotropic and kinematic components. The model has been successfully implemented in ABAQUS. The model has been used to predict the response and failure of a new BRB. The proposed model can be extended to BRBs in general. Abstract: Buckling Restrained Braces (BRBs) are installed in buildings to control lateral displacements caused by seismic events. Modelling BRBs involves predicting their hysteretic load–deformation curve and failure. We can distinguish between global models, adjusted with experimental tests, and local models, based on the constitutive equations for materials. Local models are usually implemented in FEM codes and, while they also require experimental verification, they can be extended to a wider range of geometries and materials. In this paper a new material constitutive model is proposed for predicting the hysteretic response and failure of a new all-steel BRB. This BRB offers an almost symmetric response for both compression and tensile loading because of the low interaction between the core and the restraining unit. The hysteretic behaviour is simulated using a combined isotropic and kinematic hardening as a function of the plastic flow. Damage is computed using an uncoupled analysis based on a continuum damage mechanism model. The results from the tensile and BRB tests are used to adjust and verify the model. The model has been implemented in an FEM commercial code and has proved effective in simulating the hysteretic response and predicting the failure point of the new all-steel BRB. The model presented could be extended to BRBs in general, although interaction between the core and the restraining unit would have to be taken into account.